Screening Peter to Save Paul: The Population-Level Effects of Screening Men Who Have Sex With Men for Gonorrhea and Chlamydia. Issue 9 (September 2018) - Ridpath, Alison D.; Chesson, Harrell; Marcus, Julia L.; Kirkcaldy, Robert D.; Torrone, Elizabeth A.; Aral, Sevgi O.; Bernstein, Kyle T.
Abstract : A discussion of the article by Tsoumanis et al., as well as why we screen, how we measure impact, and how we can better evaluate population-level benefits of sexually transmitted disease screening.